2012
DOI: 10.1155/2012/423520
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Postmastectomy Radiation Therapy in Ductal CarcinomaIn Situ?

Abstract: Background. DCIS treated by mastectomy ensures high local control rates. There is limited data on risk for relapse and lack of clear indication for adjuvant radiation therapy (RT). We report a retrospective review on a population of DCIS patients treated with mastectomy. The objective was to identify the overall incidence of relapse, risk factors for local recurrence, and accordingly for whom adjuvant postmastectomy RT may be considered. Methods. This is an IRB-approved retrospective study on a prospective bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 19 publications
1
24
0
2
Order By: Relevance
“…Kim and colleagues reported on ten such instances and discovered that the presence of residual normal breast tissue was a common feature. Chadha et al carried out a retrospective review of 207 patients treated by mastectomy for DCIS between 1997 and 2007. Only two (1·0 per cent) developed a local recurrence and both patients had a final mastectomy margin of less than 1 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Kim and colleagues reported on ten such instances and discovered that the presence of residual normal breast tissue was a common feature. Chadha et al carried out a retrospective review of 207 patients treated by mastectomy for DCIS between 1997 and 2007. Only two (1·0 per cent) developed a local recurrence and both patients had a final mastectomy margin of less than 1 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Both LRRs occurred in patients with margins <1 mm, and there were no LRRs among patients with margins ≥1 mm. 16 …”
Section: Discussionmentioning
confidence: 99%
“…610 Several studies have evaluated potential predictors of LRR after mastectomy for DCIS in an attempt to improve the already low rates of LRR. 1116 One of these potential predictors is margin status. There is a large body of literature regarding the relationship between margin status and risk of LRR in patients with DCIS who undergo breast-conserving therapy.…”
mentioning
confidence: 99%
“…Both LRRs occurred in patients with margins \1 mm, and there were no LRRs among patients with margins C1 mm. 16 In 2012, Owen et al from British Columbia reported on 637 patients treated with mastectomy for DCIS with a median follow-up time of 12 years. This represents the second largest published series of patients with DCIS treated with mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Several studies have evaluated potential predictors of LRR after mastectomy for DCIS in an attempt to improve the already low rates of LRR. [11][12][13][14][15][16] One of these potential predictors is margin status. There is a large body of literature regarding the relationship between margin status and risk of LRR in patients with DCIS who undergo breastconserving therapy.…”
mentioning
confidence: 99%